Synthetic single crystal diamond and its manufacturing method

By controlling the nitrogen atom concentration and forming the N3 center in synthetic single crystal diamonds, combined with high temperature and high pressure and radiation therapy, the problem of wear and defects of synthetic single crystal diamonds in tool applications is solved, and high hardness and excellent wear resistance are achieved.

JP7658373B2Active Publication Date: 2025-04-08SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022533717
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-05-14
Publication Date
2025-04-08
Estimated Expiration
2041-05-14

AI Technical Summary

Technical Problem

Existing synthetic single crystal diamonds tend to wear tips and defects in tool applications, and their quality is unstable, making it difficult to meet the needs of extended tool life.

Method used

By controlling the nitrogen atom concentration between 100 ppm and 1500 ppm in synthetic single crystal diamonds and forming an N3 center including one vacancy and three alternative nitrogen atom polymers, combining high temperature and high pressure treatment and radiation therapy, the microstructure and mechanical properties of the diamond are optimized.

Benefits of technology

The high hardness and excellent resistance to wear and defects of synthetic single crystal diamonds are achieved, extending the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658373000003
    Figure 0007658373000003
  • Figure 0007658373000004
    Figure 0007658373000004
  • Figure 0007658373000001
    Figure 0007658373000001
Patent Text Reader

Abstract

This synthetic single-crystal diamond contains nitrogen atoms at a concentration of 100-1500 ppm based on the number of atoms, and includes aggregates formed from one vacancy and three substitutional nitrogen atoms present adjacent to the vacancy, wherein the Raman shift λ'cm-1 of a peak in the first-order Raman scattering spectrum of the aforementioned synthetic single-crystal diamond, and the Raman shift λ'cm-1 of a peak in the first-order Raman scattering spectrum of a synthetic, type IIa single-crystal diamond that contains nitrogen atoms at a concentration of less than or equal to 1 ppm based on the number of atoms, satisfy formula 1 below. Formula 1 λ' – λ ≥ 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This disclosure relates to synthetic single crystal diamond and a method for producing the same. This application claims priority to Japanese Patent Application No. 2020-113053, filed on June 30, 2020. The entire contents of said Japanese Patent Application are incorporated herein by reference. [Background technology]

[0002] Due to its high hardness, single crystal diamond is widely used in tools such as cutting tools, grinding tools, wear-resistant tools, etc. The single crystal diamonds used in tools include natural diamonds and synthetic diamonds.

[0003] Most natural diamonds contain agglomerated nitrogen atoms (type Ia) as impurities. The agglomerated nitrogen atoms in diamond crystals can prevent plastic deformation and the progression of cracks that occur when diamonds are used as tools. This gives natural diamonds high mechanical strength. However, the quality of natural diamonds varies widely and the supply is unstable, limiting their use in industrial applications.

[0004] On the other hand, synthetic diamonds are of consistent quality and can be supplied steadily, so they are widely used in industrial applications.

[0005] Ordinary synthetic diamonds contain isolated substitutional nitrogen atoms as impurities (type Ib). The higher the concentration of isolated substitutional nitrogen atoms in a diamond crystal, the more likely the mechanical properties of the diamond will deteriorate. Therefore, when type Ib synthetic diamonds are used in tools, the cutting edge tends to wear and chip easily.

[0006] There are also synthetic diamonds that contain almost no nitrogen impurities (type IIa). Type IIa synthetic diamonds do not contain impurities or crystal defects that would prevent cracks from progressing, so when used in tools, they tend to chip the cutting edge.

[0007] Therefore, research is being conducted into techniques for improving the wear resistance and chipping resistance of synthetic diamond.

[0008] For example, Patent Document 1 (WO 2019 / 077888) discloses a synthetic single crystal diamond having high hardness and excellent chipping resistance. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2019 / 077888 Summary of the Invention

[0010] The synthetic single crystal diamond of the present disclosure is A synthetic single crystal diamond containing nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less based on the number of atoms, the synthetic single crystal diamond comprises an aggregate of a vacancy and three substitutional nitrogen atoms adjacent to the vacancy; The Raman shift λ'cm of the peak in the first-order Raman scattering spectrum of the synthetic single crystal diamond -1 and the Raman shift λcm of the peak in the first-order Raman scattering spectrum of synthetic type IIa single crystal diamond containing nitrogen atoms at a concentration of 1 ppm or less on an atomic number basis. -1 represents the relationship of the following formula 1: λ'-λ≧0 Equation 1 It is a synthetic single crystal diamond.

[0011] The disclosed method for producing synthetic single crystal diamond comprises: A method for producing the above synthetic single crystal diamond, comprising the steps of: A first step of synthesizing a diamond single crystal containing nitrogen atoms at a concentration of 100 ppm to 1500 ppm (based on the atomic number) by a temperature difference method using a solvent metal; a second step of irradiating the diamond single crystal with one or both of an electron beam and a particle beam having an energy of 100 MGy or more and 1000 MGy or less; This is a method for producing a synthetic single crystal diamond, comprising a third step of applying a pressure of 3 GPa or more and a temperature of 1850°C to 2300°C for 1 minute to 3600 minutes to the diamond single crystal after the second step, thereby obtaining the synthetic single crystal diamond. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is an example of a fluorescence spectrum of a synthetic single crystal diamond according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a sample chamber configuration for use in producing synthetic single crystal diamond according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Problem that this disclosure aims to solve] Due to the recent demand for longer tool life, there is a demand for synthetic single crystal diamond with superior wear resistance and chipping resistance.

[0014] It is therefore an object of the present invention to provide a synthetic single crystal diamond having high hardness and excellent chipping resistance.

[0015] [Effects of this disclosure] The synthetic single crystal diamonds of the present disclosure can have high hardness and excellent chipping resistance.

[0016] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) The synthetic single crystal diamond disclosed herein is A synthetic single crystal diamond containing nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less based on the number of atoms, the synthetic single crystal diamond comprises an aggregate of a vacancy and three substitutional nitrogen atoms adjacent to the vacancy; The Raman shift λ'cm of the peak in the first-order Raman scattering spectrum of the synthetic single crystal diamond -1 and the Raman shift λcm of the peak in the first-order Raman scattering spectrum of synthetic type IIa single crystal diamond containing nitrogen atoms at a concentration of 1 ppm or less on an atomic number basis. -1 represents the relationship of the following formula 1: λ'-λ≧0 Equation 1 It is a synthetic single crystal diamond.

[0017] The synthetic single crystal diamonds of the present disclosure can have high hardness and excellent chipping resistance.

[0018] (2) In the fluorescence spectrum of the synthetic single crystal diamond, it is preferable that an emission peak exists within the fluorescence wavelength range of 415±2 nm and / or within the fluorescence wavelength range of 420 nm or more and 470 nm or less.

[0019] According to this, synthetic single crystal diamond can have high hardness and excellent chipping resistance.

[0020] (3) In the infrared absorption spectrum of the synthetic single crystal diamond, the wave number is 1370 cm -1 Over 1385cm -1 It is preferred that the absorption peak is within the following range:

[0021] According to this, synthetic single crystal diamond can have high hardness and excellent chipping resistance.

[0022] (4) The {001} plane of the synthetic single crystal diamond <100> The Knoop hardness in the direction is preferably 100 GPa or more.

[0023] According to this, synthetic single crystal diamond can have excellent wear resistance.

[0024] (5) In a fracture strength test in which a spherical diamond indenter with a tip radius of 50 μm is pressed against the surface of the synthetic single crystal diamond at a loading rate of 100 N / min, the crack initiation load is preferably 15 N or more.

[0025] This allows synthetic single crystal diamond to have excellent chipping resistance.

[0026] (6) The method of producing a synthetic single crystal diamond according to the present disclosure comprises: A method for producing the synthetic single crystal diamond, comprising the steps of: A first step of synthesizing a diamond single crystal containing nitrogen atoms at a concentration of 100 ppm to 1500 ppm (based on the atomic number) by a temperature difference method using a solvent metal; a second step of irradiating the diamond single crystal with one or both of an electron beam and a particle beam having an energy of 100 MGy or more and 1000 MGy or less; This is a method for producing a synthetic single crystal diamond, comprising a third step of applying a pressure of 3 GPa or more and a temperature of 1850°C to 2300°C for 1 minute to 3600 minutes to the diamond single crystal after the second step, thereby obtaining the synthetic single crystal diamond.

[0027] This makes it possible to obtain a synthetic single crystal diamond having high hardness and excellent chipping resistance.

[0028] [Details of the embodiment of the present disclosure] In this specification, the expression "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.

[0029] <Form of nitrogen atoms in diamond crystals> First, in order to deepen understanding of the synthetic single crystal diamond of the present disclosure, an explanation will be given of nitrogen atoms present as impurities in the crystal, which is one of the main factors that determine the performance of diamond.

[0030] Nitrogen atoms in a diamond crystal can be classified into isolated substitutional nitrogen atoms, aggregated nitrogen atoms, etc. depending on the form in which they exist.

[0031] An isolated substitutional nitrogen atom (C center) is one in which a nitrogen atom replaces a carbon atom in a diamond crystal.

[0032] The present inventors have newly hypothesized that when an isolated substitutional nitrogen atom is contained in a diamond crystal, local tensile stress is generated in the crystal lattice around it, and this becomes the starting point for plastic deformation and fracture, resulting in a decrease in hardness and in reduced wear resistance and chipping resistance.

[0033] Synthetic single crystal diamond containing isolated substitutional nitrogen atoms has an infrared absorption spectrum measured by Fourier transform infrared spectroscopy with a wavenumber of 1130 cm -1 (i.e., wave number 1130±2 cm -1 ) shows the absorption peak.

[0034] In synthetic single crystal diamonds containing isolated substitutional nitrogen atoms, the concentration of isolated substitutional nitrogen atoms can be measured by ESR analysis (ESR: Electron Spin Resonance) because of the presence of unpaired electrons originating from the nitrogen atoms. In addition to isolated substitutional nitrogen atoms, ESR also detects signals from crystal defects that have unpaired electrons. In this case, isolated substitutional nitrogen atoms can be separated and detected by the g value or the relaxation time of the signal.

[0035] Agglomerated nitrogen atoms are those in which two or more nitrogen atoms are aggregated together and present in a diamond crystal.

[0036] The present inventors have newly assumed that the aggregated nitrogen atoms in diamond crystal can suppress the plastic deformation and crack growth that occurs when a load is applied to diamond crystal.The present inventors have newly assumed that when diamond crystal contains aggregated nitrogen atoms, the wear resistance and chipping resistance of diamond crystal are greatly improved.

[0037] The agglomerated nitrogen atoms are classified into A center (two nitrogen atom pair), H3 center (two nitrogen atom agglomeration), N3 center (three nitrogen atom agglomeration), and B center (four nitrogen atom agglomeration). collection ), B' centers or platelets, etc.

[0038] The A center (nitrogen diatomic pair) is an aggregate consisting of two nitrogen atoms, which are covalently bonded and each nitrogen atom is substituted for a carbon atom that constitutes a diamond crystal. Diamonds containing the A center (nitrogen diatomic pair) are called IaA type. Synthetic single crystal diamonds containing the A center (nitrogen diatomic pair) have an infrared absorption spectrum measured by Fourier transform infrared spectroscopy with a wave number of 1282 cm -1 (For example, wave number 1282±2 cm -1 ) shows the absorption peak.

[0039] The H3 center (two nitrogen atom aggregate) is an aggregate consisting of one vacancy and two nitrogen atoms adjacent to the vacancy, and each nitrogen atom is substituted with a carbon atom constituting a diamond crystal. In this specification, the "nitrogen atom adjacent to the vacancy" means the nitrogen atom with the shortest interatomic distance to the carbon atom (i.e., the nearest neighbor atom) when a carbon atom is assumed to exist at the position of the vacancy. The same meaning is also applied to the N3 center and B center described later.

[0040] Synthetic single crystal diamond containing an H3 center (agglomeration of two nitrogen atoms) exhibits an emission peak at a fluorescence wavelength of around 503 nm (e.g., 503±2 nm) in the fluorescence spectrum obtained by irradiating it with excitation light shorter than approximately 500 nm, for example, excitation light with a wavelength of 325 nm.

[0041] An N3 center (agglomerate of three nitrogen atoms) is an aggregate consisting of one vacancy and three nitrogen atoms adjacent to the vacancy, and each nitrogen atom replaces a carbon atom that constitutes a diamond crystal.

[0042] Synthetic single crystal diamond containing an N3 center (agglomeration of three nitrogen atoms) exhibits emission peaks at or near a fluorescence wavelength of 415 nm (for example, a fluorescence wavelength of 415±2 nm) and / or within the fluorescence wavelength range of 420 nm or more and 470 nm or less in a fluorescence spectrum obtained by irradiating the diamond with excitation light shorter than approximately 410 nm, for example, excitation light with a wavelength of 325 nm.

[0043] B center (4 nitrogen atoms) collection ) is an aggregate consisting of one vacancy and four nitrogen atoms adjacent to the vacancy, and each nitrogen atom replaces a carbon atom that constitutes the diamond crystal.

[0044] Diamonds containing four nitrogen atoms aggregated are called type IaB. Synthetic single crystal diamonds containing four nitrogen atoms aggregated have an infrared absorption spectrum measured by Fourier transform infrared spectroscopy with a wave number of 1175 cm -1 (For example, wave number 1175±2 cm -1 ) shows the absorption peak.

[0045] B' centers (also called platelets) are plate-shaped aggregates consisting of five or more nitrogen atoms and interstitial carbon, and are incorporated as inclusions within the crystal.

[0046] Diamonds containing B' centers (platelets) are called IaB' type. Synthetic single crystal diamonds containing B' centers (platelets) have an infrared absorption spectrum measured by Fourier transform infrared spectroscopy with a wave number of 1358 cm -1 Over 1385cm -1 The absorption peaks are shown below.

[0047] The present inventors have intensively studied the aggregated nitrogen atom that can improve the properties of synthetic single crystal diamond, and have newly found that N3 center has the least crystal distortion and the most stable structure.Then, by forming N3 center predominantly in synthetic single crystal diamond, the mechanical properties such as hardness, strength, wear resistance, and chipping resistance of synthetic single crystal diamond can be further improved, and thus the present disclosure has been completed.

[0048] The specific example of the synthetic single crystal diamond and its manufacturing method of the present disclosure will be described below with reference to the drawings.In the drawings of the present disclosure, the same reference numerals represent the same parts or corresponding parts.In addition, the dimensional relationship of length, width, thickness, depth, etc. is appropriately changed for the purpose of clarifying and simplifying the drawings, and does not necessarily represent the actual dimensional relationship.

[0049] [Embodiment 1: Synthetic single crystal diamond] The synthetic single crystal diamond of the present disclosure is a synthetic single crystal diamond containing nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less based on the number of atoms, the synthetic single crystal diamond containing an aggregate consisting of one vacancy and three substitutional nitrogen atoms adjacent to the vacancy, and having a Raman shift λ'cm of a peak in a first-order Raman scattering spectrum of the synthetic single crystal diamond. -1 and the Raman shift λcm of the peak in the first-order Raman scattering spectrum of synthetic type IIa single crystal diamond containing nitrogen atoms at a concentration of 1 ppm or less on an atomic number basis. -1 represents the relationship of the following formula 1: λ'-λ≧0 Equation 1 It is a synthetic single crystal diamond.

[0050] The synthetic single crystal diamond of the present disclosure can have high hardness and chipping resistance. The reason for this is not clear, but is presumed to be as follows: (i) to (iii).

[0051] (i) The synthetic single crystal diamond of the present disclosure contains nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less based on the number of atoms.Accordingly, the nitrogen atoms in the synthetic single crystal diamond tend to aggregate with each other.Therefore, the synthetic single crystal diamond tends to contain aggregated nitrogen atoms, and the wear resistance and chipping resistance of the diamond crystal are improved.

[0052] (ii) The synthetic single crystal diamond of the present disclosure comprises an aggregate consisting of one vacancy and three substitutional nitrogen atoms adjacent to the vacancy. That is, the synthetic single crystal diamond of the present disclosure comprises an N3 center. The N3 center can suppress the plastic deformation and crack growth that occurs when a load is applied to the synthetic single crystal diamond. Therefore, the synthetic single crystal diamond has improved chipping resistance.

[0053] Furthermore, among the aggregated nitrogen atoms, the N3 center has the least crystal distortion and the most stable structure. Therefore, the synthetic single crystal diamond of the present disclosure containing the N3 center can have high hardness and excellent wear resistance.

[0054] (iii) the Raman shift λ'cm of the peak in the first-order Raman scattering spectrum of the synthetic single crystal diamond of the present disclosure; -1 and the Raman shift λcm of the peak in the first-order Raman scattering spectrum of synthetic type IIa single crystal diamond containing nitrogen atoms at a concentration of 1 ppm or less on an atomic number basis. -1 represents the relationship of the following formula 1. λ'-λ≧0 Equation 1

[0055] In the synthetic single crystal diamond of the present disclosure, the above formula 1 is satisfied, tensile stress is almost absent, and compressive stress is generated.Therefore, even if isolated substitutional nitrogen atoms exist, the isolated substitutional nitrogen atoms do not become the starting point of plastic deformation or fracture.Therefore, the synthetic single crystal diamond of the present disclosure can have excellent strength and fracture resistance.The details of the relationship between the above formula 1 and the internal stress of synthetic single crystal diamond will be described later.

[0056] <Nitrogen atom concentration> The synthetic single crystal diamond of the present disclosure contains nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less based on the number of atoms (hereinafter also referred to as "nitrogen atom concentration"). When the nitrogen atom concentration is 100 ppm or more, the nitrogen atoms in the synthetic single crystal diamond tend to form aggregated nitrogen atoms. When the nitrogen atom concentration is 1500 ppm or less, the synthetic single crystal diamond can have high hardness and excellent chipping resistance.

[0057] The lower limit of the nitrogen atom concentration in the synthetic single crystal diamond can be 100 ppm or more, 200 ppm or more, or 300 ppm or more. The upper limit of the nitrogen atom concentration in the synthetic single crystal diamond can be 1500 ppm or less, 1400 ppm or less, or 1300 ppm or less. The nitrogen atom concentration in the synthetic single crystal diamond can be 100 ppm or more and 1500 ppm or less, 100 ppm or more and 1400 ppm or less, 100 ppm or more and 1300 ppm or less, 200 ppm or more and 1500 ppm or less, 200 ppm or more and 1400 ppm or less, 200 ppm or more and 1300 ppm or less, 300 ppm or more and 1500 ppm or less, 300 ppm or more and 1400 ppm or less, or 300 ppm or more and 1300 ppm or less.

[0058] The nitrogen atom concentration in synthetic single crystal diamond can be measured by secondary ion mass spectrometry (SIMS).

[0059] <Agglomerated nitrogen atoms> (N3 Center) The synthetic single crystal diamond of the present disclosure comprises an aggregate consisting of one vacancy and three substitutional nitrogen atoms adjacent to the vacancy. That is, the synthetic single crystal diamond of the present disclosure comprises an N3 center. The N3 center can suppress the plastic deformation and crack growth that occurs when a load is applied to the synthetic single crystal diamond. Therefore, the synthetic single crystal diamond has improved chipping resistance.

[0060] Furthermore, among the aggregated nitrogen atoms, the N3 center has the least crystal distortion and the most stable structure. Therefore, the synthetic single crystal diamond of the present disclosure containing the N3 center can have high hardness and excellent wear resistance.

[0061] The fact that synthetic single crystal diamond contains N3 center can be confirmed by the fluorescence spectrum obtained by irradiating synthetic single crystal diamond with excitation light shorter than about 410nm, for example, excitation light with wavelength 325nm.Specifically, in the fluorescence spectrum obtained by irradiating synthetic single crystal diamond with excitation light with wavelength 325nm, if there is an emission peak in either or both of the fluorescence wavelength range of 415±2nm and the fluorescence wavelength range of 420nm or more and 470nm or less, synthetic single crystal diamond is judged to contain N3 center.

[0062] The peak in the range of 415±2 nm in fluorescence wavelength is an emission peak corresponding to the zero phonon line of the N3 center, and the emission peak in the range of 420 nm to 470 nm in fluorescence wavelength is an emission peak corresponding to the subband (phonon sideband) of the N3 center. The emission peak in the range of 420 nm to 470 nm in fluorescence wavelength is observed as one or more mountain-shaped peaks within the range. At least one of the mountain-shaped peaks shows the maximum intensity within the range.

[0063] An example of a fluorescence spectrum obtained by irradiating a synthetic single crystal diamond according to an embodiment of the present disclosure (hereinafter also referred to as "this embodiment") with excitation light having a wavelength of 325 nm is shown in Figure 1. In Figure 1, the X-axis indicates the fluorescence wavelength (nm) and the Y-axis indicates the emission intensity. In the fluorescence spectrum shown in Figure 1, there is an emission peak (indicated by arrow N3) within the fluorescence wavelength range of 415±2 nm, and an emission peak (indicated by arrow S) within the fluorescence wavelength range of 420 nm or more and 470 nm or less.

[0064] The presence of N3 centers in synthetic single crystal diamonds can also be confirmed by UV-Vis spectroscopy. Specifically, when an absorption spectrum at a wavelength of 393 nm is present in the UV-Vis spectroscopy, the synthetic single crystal diamond is judged to contain N3 centers.

[0065] (B' center (platelet)) In the infrared absorption spectrum of the synthetic single crystal diamond of the present disclosure, the wave number is 1370 cm -1 Over 1385cm -1 It is preferred that there is an absorption peak within the following range: The absorption peak originates from the B' centre (platelet) in the synthetic single crystal diamond.

[0066] In the infrared absorption spectrum of synthetic single crystal diamond, the wave number is 1370 cm -1 Over 1385cm -1 If the absorption peak exists within the following range, the size of the aggregate of nitrogen atoms contained in the B' center (platelet) is appropriate, and the growth of plastic deformation and cracks can be prevented, and the aggregate is unlikely to become the starting point of fracture. Therefore, the synthetic single crystal diamond can have high hardness and excellent strength.

[0067] Generally, synthetic single crystal diamonds containing B' centers (platelets) have a wave number of 1358 cm in the infrared absorption spectrum. -1 Over 1385cm -1 The absorption peak is shown below. However, the wave number is 1370 cm -1 Smaller range (wave number 1358 cm -1 wave number 1370cm or more -1 If there is an absorption peak at wavenumber 1358 cm or less in the infrared absorption spectrum of synthetic single crystal diamond, the B' center (platelet) aggregates in the crystal are too large and can become the starting point of fracture, which is undesirable. -1 wave number 1370cm or more -1 It is preferred that there be no absorption peaks within the range of less than 100 nm.

[0068] (Other agglomerated nitrogen atoms) The synthetic single crystal diamond of the present disclosure can include A center (two nitrogen atom pair), H3 center (two nitrogen atom aggregate), B center (four nitrogen atom aggregate) and B' center. The nitrogen atom aggregate contained therein can suppress the propagation of cracks in single crystal diamond. Therefore, the synthetic single crystal diamond can have excellent chipping resistance.

[0069] The presence of the A center in a synthetic single crystal diamond can be confirmed by an infrared absorption spectrum measured by Fourier transform infrared spectroscopy. -1 Near (for example, 1282±2cm -1 ) is present, the synthetic single crystal diamond is judged to contain an A center.

[0070] The fact that synthetic single crystal diamond contains H3 center can be confirmed by the fluorescence spectrum obtained by irradiating excitation light with a wavelength of 325 nm.Specifically, when the emission peak exists in the vicinity of the fluorescence wavelength of 503 nm (for example, 503±2 nm) in the fluorescence spectrum, the synthetic single crystal diamond is judged to contain H3 center.

[0071] The presence of a B center in a synthetic single crystal diamond can be confirmed by an infrared absorption spectrum measured by Fourier transform infrared spectroscopy. Specifically, in the infrared absorption spectrum, -1 Near (for example, 1175±2cm -1 ) is present, the synthetic single crystal diamond is judged to contain a B center.

[0072] <Lonely substituted nitrogen atom> The synthetic single crystal diamond of the present disclosure preferably does not contain isolated substitutional nitrogen atoms (C centers), which allows the synthetic single crystal diamond of the present disclosure to have high hardness and excellent chipping resistance.

[0073] The absence of isolated substitutional nitrogen atoms in synthetic single crystal diamonds can be determined by the infrared absorption spectrum measured by Fourier transform infrared spectroscopy. Single crystal diamonds containing isolated substitutional nitrogen atoms have an infrared absorption spectrum measured by Fourier transform infrared spectroscopy with a wave number of 1130 cm -1 (i.e., 1130±2cm -1 ) in the infrared absorption spectrum of synthetic single crystal diamond. -1 By confirming that no absorption peak derived from an isolated substitutional nitrogen atom is present within the range, it can be determined that no isolated substitutional nitrogen atom is contained.

[0074] In the infrared absorption spectrum, the wave number is 1130±2 cm -1 In the range, there is a shoulder in the absorption spectrum of aggregated nitrogen atoms other than isolated substitutional nitrogen, and it is unclear whether the shoulder is an absorption peak derived from isolated substitutional nitrogen atoms, the presence or absence of isolated substitutional nitrogen atoms can be determined by ESR analysis. If there is no isolated substitutional nitrogen atom in synthetic single crystal diamond, there is no unpaired electron in synthetic single crystal diamond. Therefore, when ESR analysis is performed on such synthetic single crystal diamond, no signal is detected. This makes it possible to confirm that there is no isolated substitutional nitrogen atom in synthetic single crystal diamond.

[0075] <Infrared absorption spectrum> When a diamond crystal contains C, A, B, and B' centers (platelets), absorption peaks originating from each center are observed in the infrared absorption spectrum of the diamond crystal measured by Fourier transform infrared spectroscopy. Since the waveforms of each center overlap, the presence or absence and amount of each center cannot be determined from the intensity value at each wave number alone. On the other hand, by considering the approximate waveform of each center from a relative comparison of the intensity at each wave number, it is possible to determine the presence or absence of each center and to qualitatively evaluate the content ratio of each center.

[0076] <1st-order Raman scattering spectrum> The Raman shift λ'cm of the peak in the first-order Raman scattering spectrum of the synthetic single crystal diamond of the present disclosure -1 and nitrogen atoms at a concentration of 1 ppm or less based on the number of atoms. Mutual The Raman shift λcm of the peak in the first-order Raman scattering spectrum of grown type IIa single crystal diamond -1 represents the relationship of the following formula 1. λ'-λ≧0 Equation 1

[0077] One of the factors that affect the wear resistance and fracture resistance of diamond is the state of internal stress in the crystal. When tensile stress exists in diamond crystal, the diamond crystal is easily plastically deformed or broken from the point where tensile stress occurs, and wear resistance and fracture resistance are reduced. On the other hand, when compressive stress exists in diamond crystal, fracture resistance is improved. Therefore, by making the state of internal stress of diamond crystal as small as possible, or making compressive stress predominant, the wear resistance and fracture resistance of single crystal diamond can be improved.

[0078] The state of internal stress in synthetic single crystal diamond can be determined by the Raman shift λ' (cm -1 ) in a concentration of 1 ppm or less based on the number of atoms, and the Raman shift λ (cm) of the peak in the first-order Raman scattering spectrum of a synthetic type IIa single crystal diamond (hereinafter also referred to as a standard sample or a synthetic type IIa single crystal diamond). -1 ) can be evaluated. Specifically, the state of internal stress in the synthetic single crystal diamond can be evaluated based on the magnitude of the peak position shift represented by the difference between λ' and λ (λ'-λ). The reason for this is explained below.

[0079] The synthetic type IIa single crystal diamond used as the standard sample means a single crystal diamond that is high purity and free of lattice defects and internal strain, synthesized by the temperature difference method under high temperature and high pressure. For example, it is commercially available as high purity type IIa single crystal diamond manufactured by Sumitomo Electric Co., Ltd. Synthetic type IIa single crystal diamond has a nitrogen atom concentration based on the atomic number of 1 ppm or less, or 0 ppm to 1 ppm, and contains almost no nitrogen atoms, so there is no internal stress in the diamond crystal. Synthetic type IIa single crystal diamond also shows a single sharp and strong peak in the first-order Raman scattering spectrum. Usually, the Raman shift of this peak is 1332 cm -1 From 1333cm -1 The Raman shift value varies depending on the temperature of the environment during measurement. In this specification, the Raman shift is a value measured at room temperature (20° C. or higher and 25° C. or lower).

[0080] When isolated substitutional nitrogen atoms exist in a diamond crystal, the Raman shift shifts to a lower frequency side than that of synthetic type IIa single crystal diamond. At this time, tensile stress originating from isolated substitutional nitrogen atoms occurs in the diamond crystal. On the other hand, when isolated substitutional nitrogen atoms do not exist in a diamond crystal and aggregated nitrogen atoms exist, the Raman shift shifts to a higher frequency side than that of synthetic type IIa single crystal diamond. At this time, tensile stress does not occur in the diamond crystal, or compressive stress occurs.

[0081] Therefore, the Raman shift λ' (cm -1 ) and the Raman shift λ (cm) of synthetic type IIa single crystal diamond -1 ) the internal stress state of the synthetic single crystal diamond can be evaluated.

[0082] Based on the above findings, the present inventors have determined that λ'(cm -1 ) and λ(cm -1As a result of extensive investigations into the relationship between the magnitude of the peak position shift, represented by the difference (λ'-λ), and the fracture resistance and hardness of a synthetic single crystal diamond, it has been found that when (λ'-λ) satisfies the relationship in Formula 1 below, the synthetic single crystal diamond has high hardness as well as excellent fracture resistance. λ'-λ≧0 Equation 1

[0083] When (λ'-λ) satisfies the relationship of formula 1, the amount of isolated substitutional nitrogen atoms in the synthetic single crystal diamond is sufficiently reduced, and the synthetic single crystal diamond can have excellent chipping resistance and high hardness. The lower limit of (λ'-λ) can be 0 or more, 0.05 or more, 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, or 0.3 or more. The upper limit of (λ'-λ) can be 2 or less, or 1 or less. (λ'-λ) can be 0 or more and 2 or less, 0 or more and 1 or less, 0.05 or more and 2 or less, 0.05 or more and 1 or less, 0.1 or more and 2 or less, 0.1 or more and 1 or less, 0.15 or more and 2 or less, 0.15 or more and 1 or less, 0.2 or more and 2 or less, 0.2 or more and 1 or less, 0.25 or more and 2 or less, 0.25 or more and 1 or less, 0.3 or more and 2 or less, or 0.3 or more and 1 or less.

[0084] The Raman shift of the peak in the first-order Raman scattering spectrum of synthetic single crystal diamond and a standard sample can be measured using a Raman microscope. The measurement is performed at room temperature (20°C to 25°C) using a laser with a wavelength of 532 nm as the excitation light.

[0085] An arbitrary surface of a synthetic single crystal diamond is polished, and the Raman shift (λ') of the peak in the first-order Raman scattering spectrum of the polished surface is measured. An arbitrary surface of a high-purity synthetic type IIa single crystal diamond, which is a standard sample, is polished, and the Raman shift (λ) of the peak in the first-order Raman scattering spectrum of the polished surface is measured.

[0086] λ' and λ are the wavenumbers at which the first-order Raman scattering spectrum signal is strongest. The peak shape is evaluated by peak fitting using a Lorentzian function or a Gaussian function. When measuring samples and standard samples, the temperature change of the detector and optical system of the Raman spectrometer is kept within ±1°C.

[0087] The amount of peak position shift can be obtained by calculating the value of (λ'-λ).

[0088] <Knoop hardness>

[0089] The synthetic single crystal diamond according to the present embodiment has a {001} plane. <100> Knoop hardness in the {001} direction (hereafter referred to as {001} <100> The Knoop hardness is preferably 100 GPa or more. In this specification, a generic plane orientation including a plane orientation that is equivalent in terms of crystal geometry is indicated by {}, and a generic direction including a direction that is equivalent in terms of crystal geometry is indicated by <>. {001} <100> Synthetic single crystal diamond, with a Knoop hardness of 100 GPa or more, is harder and more wear-resistant than natural diamonds, which contain nitrogen.

[0090] {001} <100> The lower limit of the Knoop hardness scale is 105GP. a The pressure can be 110 GPa or more, or 115 GPa or more. <100> The upper limit of the Knoop hardness is not particularly limited, but from the viewpoint of manufacturing, it can be set to, for example, 150 GPa or less. <100> The Knoop hardness can be 100 GPa or more and 150 GPa or less, 105 GPa or more and 150 GPa or less, 110 GPa or more and 150 GPa or less, or 115 GPa or more and 150 GPa or less.

[0091] {001} <100> The method for evaluating the Knoop hardness (hereinafter referred to as HK, in GPa units) is explained. First, the {001} plane of a synthetic single crystal diamond is <100> An indentation is made in the direction of the specimen with a load of 4.9 N. The diagonal line a (μm) of the longer side of the indentation is measured and calculated from the following formula A as {001} <100> Calculate the Knoop hardness (HK).

[0092] HK=14229×4.9 / a 2 Formula A

[0093] <Crack generation load> The synthetic single crystal diamond of the present disclosure preferably has a crack initiation load of 15 N or more in a fracture strength test in which a spherical diamond indenter with a tip radius (R) of 50 μm is pressed against the surface of the synthetic single crystal diamond at a load rate of 100 N / min. If the crack initiation load is 15 N or more, the synthetic single crystal diamond has excellent fracture strength and chipping resistance, and is less likely to chip at the cutting edge when used as a tool material.

[0094] The lower limit of crack initiation load can be 17N or more, 20N or more, 25N or more, 30N or more. The upper limit of crack initiation load is not particularly limited, but from the viewpoint of manufacturing, it is, for example, 50N or less. The crack initiation load of synthetic single crystal diamond can be 15N or more and 50N or less, 17N or more and 50N or less, 20N or more and 50N or less, 25N or more and 50N or less, 30N or more and 50N or less.

[0095] The specific method for the fracture strength test is as follows: A spherical diamond indenter with a tip radius (R) of 50 μm is pressed against the sample, a load is applied to the sample at a loading rate of 100 N / min, and the load at the moment when a crack appears in the sample (crack initiation load) is measured. The moment when a crack appears is measured with an AE sensor. A higher crack initiation load indicates a higher strength of the sample and better fracture resistance.

[0096] If an indenter with a tip radius (R) smaller than 50 μm is used as the measurement indenter, the sample will undergo plastic deformation before cracks occur, making it impossible to accurately measure the strength against cracks. In addition, although measurements can be made using an indenter with a tip radius (R) larger than 50 μm, there are problems such as the load required for cracks to occur being larger, the contact area between the indenter and the sample being larger, the effect of the sample's surface accuracy on the measurement accuracy, and the effect of the crystal orientation of the single crystal being significant. Therefore, it is preferable to use an indenter with a tip radius (R) of 50 μm for fracture strength tests of synthetic single crystal diamonds.

[0097] [Embodiment 2: Method for producing synthetic single crystal diamond] An example of the method for producing the synthetic single crystal diamond of embodiment 1 is described below. Note that the synthetic single crystal diamond of embodiment 1 is not limited to the one produced by the following production method, and may be produced by other production methods.

[0098] The method for producing synthetic single crystal diamond of the present disclosure is the method for producing synthetic single crystal diamond of embodiment 1, and comprises a first step of synthesizing a diamond single crystal containing nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less, based on the atomic number, by a temperature difference method using a solvent metal, a second step of irradiating the diamond single crystal with one or both of an electron beam and a particle beam that imparts an energy of 100 MGy or more and 1000 MGy or less, and a third step of applying a pressure of 3 GPa or more and a temperature of 1850°C or more and 2300°C or less for 1 minute or more and 3600 minutes or less to the diamond single crystal after the second step, to obtain the synthetic single crystal diamond.

[0099] (1st step) A diamond single crystal can be produced by the temperature difference method, for example, using a sample chamber having the configuration shown in FIG.

[0100] As shown in FIG. 2, in a sample chamber 10 used for producing a diamond single crystal 1, an insulator 2, a carbon source 3, a solvent metal 4, and a seed crystal 5 are arranged in a space surrounded by a graphite heater 7, and a pressure medium 6 is arranged outside the graphite heater 7. The temperature difference method is a method in which a vertical temperature gradient is provided inside the sample chamber 10, and the high temperature part (T high ) with 3 carbon sources and low temperature section (T low This synthesis method involves placing a diamond seed crystal 5 in a carbon source 3, disposing a solvent metal 4 between the carbon source 3 and the seed crystal 5, and maintaining the temperature at which the solvent metal 4 dissolves and the pressure at which diamond becomes thermally stable, thereby growing a diamond single crystal 1 on the seed crystal 5.

[0101] It is preferable to use diamond powder as the carbon source 3. Graphite or pyrolytic carbon can also be used. As the solvent metal 4, one or more metals selected from iron (Fe), cobalt (Co), nickel (Ni), manganese (Mn), etc., or an alloy containing these metals can be used.

[0102] To the carbon source 3 or the solvent metal 4, nitrogen sources such as, for example, nitrides such as iron nitride (Fe2N, Fe3N), aluminum nitride (AlN), phosphorus nitride (P3N4), silicon nitride (Si3N4), and organic nitrogen compounds such as melamine and sodium azide can be added as a single substance or mixture. Diamond or graphite containing a large amount of nitrogen can also be added as a nitrogen source. This allows nitrogen atoms to be contained in the diamond single crystal that is synthesized. At this time, the nitrogen atoms in the diamond single crystal are mainly present as isolated substitutional nitrogen atoms.

[0103] The concentration of the nitrogen source in the carbon source 3 or the solvent metal 4 is adjusted so that the concentration of nitrogen atoms in the diamond single crystal to be synthesized is 100ppm or more and 1500ppm or less based on the atomic number.For example, in the carbon source, the concentration of the nitrogen atoms derived from the nitrogen source based on the atomic number can be 200ppm or more and 3000ppm or less.In addition, in the solvent metal, for example, when the solvent metal is an alloy made of iron-cobalt-nickel and the nitrogen source is Fe3N, the concentration of the nitrogen source can be 0.01% by mass or more and 0.2% by mass or less.

[0104] The solvent metal 4 may further contain one or more elements selected from the group consisting of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), copper (Cu), zirconium (Zr), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), hafnium (Hf), tantalum (Ta), tungsten (W), osmium (Os), iridium (Ir), and platinum (Pt).

[0105] (2nd process) Next, the resulting diamond single crystal is irradiated with either or both of an electron beam and a particle beam imparting an energy of 100 MGy to 1000 MGy, which introduces lattice defects into the diamond single crystal and forms vacancies.

[0106] If the amount of energy to be irradiated is less than 100MGy, the introduction of lattice defects may be insufficient. On the other hand, if the amount of energy is more than 1000MGy, excessive vacancies may be generated, and the crystallinity may be greatly reduced. Therefore, the amount of energy is preferably 100MGy or more and 1000MGy or less.

[0107] As the particle beam, neutron beam or proton beam can be used. The irradiation conditions are not particularly limited as long as the energy of 100MGy or more and 1000MGy or less can be given to the diamond single crystal. For example, when using an electron beam, the irradiation energy can be 4.6MeV or more and 4.8MeV or less, the current can be 2mA or more and 5mA or less, and the irradiation time can be 30 hours or more and 45 hours or less.

[0108] (3rd step) Next, a pressure of 3 GPa or more and a temperature of 1850°C to 2300°C are applied to the diamond single crystal after the second step for 1 minute to 3600 minutes to obtain a synthetic single crystal diamond. As a result, isolated substitutional nitrogen atoms in the diamond single crystal move through the vacancies and aggregate to become aggregated nitrogen atoms.

[0109] By setting the temperature of the third step to 1850°C or higher, the movement of nitrogen atoms in the diamond single crystal is promoted, and the formation of an aggregate (N3 center) consisting of one vacancy and three substitutional nitrogen atoms adjacent to the vacancy is promoted. If the temperature of the third step is less than 1850°C, it is difficult to form the N3 center. The upper limit of the temperature of the third step is preferably 2300°C or lower from the viewpoint of cost and productivity.

[0110] On the other hand, when diamond single crystal is heated to 1850℃ or higher under normal pressure, diamond single crystal is graphitized. As a result of intensive research, the present inventors have newly discovered that diamond single crystal is subjected to a temperature of 1850℃ or higher under a high pressure of 3GPa or higher for 1 minute to 3600 minutes, and the diamond single crystal is not graphitized, and the movement of nitrogen atoms in the diamond single crystal is promoted.

[0111] The time for which the diamond single crystal is subjected to a temperature of 1850°C or higher under a high pressure of 3 GPa or higher is 1 minute or more and 3600 minutes or less. The time for which the diamond single crystal is subjected to a temperature of 1850°C or higher under a high pressure of 3 GPa or higher can be 60 minutes or more and 360 minutes or less. The pressure at this time can be 3 GPa or more and 20 GPa or less.

[0112] The second and third steps can be repeated two or more times, with each being performed once as one cycle, to promote aggregation of isolated substitutional nitrogen atoms in the diamond single crystal.

[0113] [Appendix 1] The synthetic single crystal diamond of the present disclosure preferably does not include isolated substitutional nitrogen atoms, which further enhances the hardness and chipping resistance of the synthetic single crystal diamond.

[0114] [Appendix 2] In the infrared absorption spectrum of the synthetic single crystal diamond disclosed herein, the wave number is 1130±2 cm -1 It is preferred that there be no absorption peak within this range, which further enhances the hardness and chipping resistance of the synthetic single crystal diamond.

[0115] [Appendix 3] In the infrared absorption spectrum of the synthetic single crystal diamond of the present disclosure, the wave number is 1358 cm -1 wave number 1370cm or more -1 Preferably, there is no absorption peak within the range of less than 100 nm, which further enhances the hardness and chipping resistance of the synthetic single crystal diamond.

[0116] [Appendix 4] The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 100 ppm and equal to or less than 1400 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 100 ppm and equal to or less than 1300 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 200 ppm and equal to or less than 1500 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 200 ppm and equal to or less than 1400 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 200 ppm and equal to or less than 1300 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 300 ppm and equal to or less than 1500 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 300 ppm and equal to or less than 1400 ppm. The nitrogen atom concentration in the synthetic single crystal diamond of the present disclosure may be equal to or greater than 300 ppm and equal to or less than 1300 ppm.

[0117] [Appendix 5] In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0 or greater and 1 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.05 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.05 or more and 1 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.1 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.1 or more and 1 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.15 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.15 or greater and 1 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.2 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.2 or more and 1 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.25 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.25 or more and 1 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.3 or more and 2 or less. In the synthetic single crystal diamond of the present disclosure, the above (λ'-λ) can be 0.3 or more and 1 or less. EXAMPLES

[0118] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.

[0119] [Growth of synthetic single crystal diamond] <Sample 2, Sample 4 to Sample 7> (1st step) Using the sample chamber having the configuration shown in Figure 2, diamond single crystals are synthesized by the temperature difference method using a solvent metal.

[0120] An alloy of iron, cobalt and nickel was prepared as a solvent metal. nitrogen Iron nitride (FeN) powder is added as an elemental supply source. The concentration of iron nitride in the solvent metal is shown in the "Iron nitride concentration in solvent metal (mass%)" column under "Manufacturing conditions" in Table 1. For example, in sample 2, the concentration of iron nitride in the solvent metal is 0.02 mass%.

[0121] Diamond powder is used as the carbon source, and about 0.5 mg of a single diamond crystal is used as the seed crystal. The temperature inside the sample chamber is adjusted with a heater so that there is a temperature difference of several tens of degrees between the high-temperature part where the carbon source is placed and the low-temperature part where the seed crystal is placed. Using an ultra-high pressure generator, the pressure is controlled to 5.5 GPa and the temperature of the low-temperature part is controlled within the range of 1370°C ± 10°C (1360°C to 1380°C), and maintained for 60 hours to synthesize a single diamond crystal on the seed crystal.

[0122] (2nd process) Next, the obtained diamond single crystal is irradiated with an electron beam. The irradiation conditions are: irradiation energy 4.6 MeV, current 2 mA, and irradiation time 30 hours. These irradiation conditions give the diamond single crystal an energy of 100 MGy.

[0123] (3rd step) Next, the diamond single crystal after electron beam irradiation is subjected to 60 minutes of treatment at normal pressure (sample 4) or at a high pressure of 3 GPa or more (sample 2, samples 5 to 7, and indicated as "high pressure" in Table 1) at the temperature indicated in the "Third step (60 minutes)" column of "Manufacturing conditions" in Table 1 to obtain a synthetic single crystal diamond. For example, in sample 2, a pressure of 3 GPa or more (high pressure) and a temperature of 2300°C are applied to the diamond single crystal for 60 minutes.

[0124] <Sample 1> For sample 1, a diamond single crystal is synthesized by the same first step as for sample 2. For sample 1, the second and third steps are not carried out.

[0125] <Sample 3> For sample 3, a diamond single crystal is synthesized by the same first step as for sample 4. For sample 1, the second and third steps are not carried out.

[0126] [Table 1]

[0127] <Evaluation> For the synthetic single crystal diamonds of samples 2 and 4 to 7, and the diamond single crystals of samples 1 and 3 (hereinafter also referred to as "synthetic single crystal diamond / diamond single crystal"), nitrogen concentration measurements, Raman spectroscopic analysis, fluorescence spectrum measurements, infrared spectroscopic analysis, Knoop hardness measurements, and fracture strength tests were performed.

[0128] (Measurement of nitrogen atom concentration) The concentration of nitrogen atoms in each sample of synthetic single crystal diamond / diamond single crystal was determined by SIMS analysis based on the atomic number. The results are shown in the "Nitrogen atom concentration (ppm)" column of "Synthetic single crystal diamond / diamond single crystal" in Table 2.

[0129] (Raman spectroscopy) Raman shift λ'cm of the peak in the first-order Raman scattering spectrum of each synthetic single crystal diamond / diamond single crystal sample -1 and the Raman shift λcm of the peak in the first-order Raman scattering spectrum of synthetic type IIa single crystal diamond (high-purity type IIa single crystal diamond manufactured by Sumitomo Electric Co., Ltd.) containing nitrogen atoms at a concentration of 1 ppm or less on an atomic number basis. -1 is measured by microscopic Raman spectroscopy, and the value of (λ'-λ) is calculated. The specific measurement method is described in the first embodiment, and therefore the description will not be repeated. The results are shown in Table 2, in the "Raman spectrum" of "Synthetic single crystal diamond / diamond single crystal" as "(λ'-λ) (cm -1 ) column.

[0130] (Fluorescence spectrum) The surface of each synthetic single crystal diamond / diamond single crystal sample is mirror-polished, and then irradiated with excitation light having a wavelength of 325 nm to measure the fluorescence spectrum.

[0131] In the fluorescence spectrum, the presence or absence of an emission peak within the fluorescence wavelength range of 415±2 nm, and the presence or absence of an emission peak within the fluorescence wavelength range of 420 nm to 470 nm are confirmed. The results are shown in the "Emission peak (emission intensity) within the 415±2 nm range" and "420-470 nm subband (maximum emission intensity)" columns of "Fluorescence spectrum" for "Synthetic single crystal diamond / single crystal diamond" in Table 2.

[0132] When an emission peak is present within the range of 415±2 nm of the fluorescence wavelength, the emission intensity of the peak is shown in parentheses. However, the emission intensity does not necessarily correspond to the content of the N3 center (emission intensity changes depending on the state of other impurities and crystal defects).

[0133] If an emission peak is present within the fluorescent wavelength range of 420 nm to 470 nm, the maximum emission intensity of the peak is shown in parentheses. However, the maximum emission intensity does not necessarily correspond to the content of the N3 center (emission intensity changes depending on the state of other impurities and crystal defects).

[0134] In all samples (sample 2, and samples 5 to 7) that have a peak within the fluorescence wavelength range of 415±2 nm, an emission peak is also observed within the fluorescence wavelength range of 420 nm or more and 470 nm or less. In all samples (sample 1, sample 3, and sample 4) that had "no" peak within the fluorescence wavelength range of 415±2 nm, no emission peak was observed within the fluorescence wavelength range of 420 nm or more and 470 nm or less.

[0135] If there is an emission peak in either or both of the range of 415±2 nm in fluorescence wavelength and the range of 420 nm to 470 nm in fluorescence wavelength, the N3 center is marked as "present." If there is no emission peak in either range, the N 3 The results are shown in the "N3 center" column of "Fluorescence spectrum" for "Synthetic single crystal diamond / single crystal diamond" in Table 2.

[0136] (Infrared spectroscopy) Each synthetic single crystal diamond / diamond sample was processed into a plate with a thickness of about 1 mm, and the two light-transmitting surfaces were polished to a mirror finish. light method The absorbance in the infrared region is measured by this method, and an infrared absorption spectrum is created.

[0137] In the infrared absorption spectrum, excluding absorption by other centers, the wavenumber is 1282 ± 2 cm -1 If there is an absorption peak at wavenumber 1282±2 cm, the A center is considered to be "present." -1 When there is no absorption peak in the A center, it is considered to be “absent.” The results are shown in the “A center” column of “Infrared absorption spectrum” for “Synthetic single crystal diamond / Diamond single crystal” in Table 2.

[0138] In the infrared absorption spectrum, excluding absorption by other centers, the wavenumber is 1175 ± 2 cm -1 If there is an absorption peak at wavenumber 1175±2cm, the B center is considered to be "present". -1 When there is no absorption peak in the B center, it is considered to be “absent.” The results are shown in the “B center” column of “Infrared absorption spectrum” for “Synthetic single crystal diamond / Diamond single crystal” in Table 2.

[0139] In the infrared absorption spectrum, excluding absorption by other centers, the wavenumber is 1130 ± 2 cm -1 If there is an absorption peak at wavenumber 1130±2cm, the C center is considered to be "present". -1 When there is no absorption peak in the spectrum, the C center is deemed to be “absent.” The results are shown in the “C center” column of “Infrared absorption spectrum” for “Synthetic single crystal diamond / Diamond single crystal” in Table 2.

[0140] In the infrared absorption spectrum, excluding absorption by other centers, the wavenumber is 1370 to 1385 cm -1 If there is an absorption peak at wavenumber 1370-1385 cm, the B' center (platelet) is considered to be present. -1When there is no absorption peak, the B' center (platelet) is deemed to be "absent." The results are shown in the "B' center / platelet" column of "Infrared absorption spectrum" for "Synthetic single crystal diamond / Diamond single crystal" in Table 2.

[0141] In addition, synthetic single crystal diamond containing a B' center (platelet) has a wave number of 1358 cm in the infrared absorption spectrum. -1 Over 1385cm -1 The absorption peak is shown below. However, the wave number is 1370 cm -1 Smaller range (wave number 1358 cm -1 wave number 1370cm or more -1 If there is an absorption peak at a wave number of 1358 cm or less, the B' center (platelet) aggregates in the crystal are too large and can become the starting point of destruction, which is not preferable. -1 wave number 1370cm or more -1 There is no absorption peak below this range.

[0142] For reference, the phonon absorption of diamond is at a wave number of 2160 cm -1 The wave number is 1282 cm when the absorbance is 1. -1 (A center) absorbance value, wavenumber 1175 cm -1 (B center) absorbance value, wavenumber 1130cm -1 (C center) absorbance value, wavenumber 1370cm -1 Over 1385cm -1 The absorbance value of the following peaks, wavenumber 1358 cm -1 wave number 1370cm or more -1 The absorbance value of the peak less than this is calculated. The results are shown in the "I(1282) / I(2160)", "I(1175) / I(2160)", "I(1130) / I(2160)", "I(1370-1385) / I(2160)", and "I(1358-1370) / I(2160)" columns of the "Infrared Absorption Spectrum" of "Synthetic Single Crystal Diamond / Diamond Single Crystal" in Table 2.

[0143] Regarding I(1282) / I(2160), the value of I(1282) / I(2160) is larger in sample 3 without the A center than in sample 2 with the A center. This is because sample 3 has a large amount of nitrogen in the C center, and the wavenumber 1282 cm originating from the shoulder of the absorption spectrum of this C center. -1 This is due to the strong absorption at 1000 nm, and does not indicate that Sample 3 contains the A center.

[0144] Regarding I(1175) / I(2160), the value of I(1175) / I(2160) is larger for sample 3 without the B center than for samples 2, 4, and 5 with the B center. This is because sample 3 has a large amount of nitrogen in the C center, and the wavenumber 1175 cm originating from the shoulder of the absorption spectrum of this C center. -1 This is due to the strong absorption at 1000 nm, and does not indicate that Sample 3 contains a B center.

[0145] Regarding I(1130) / I(2160), Samples 4 to 7 without the C center have a larger I(1130) / I(2160) value than Sample 1 with the C center. This is because Samples 4 to 7 have a large amount of nitrogen in the A and B centers, and the wavenumber 1130 cm originating from the shoulders in the absorption spectra of these A and B centers. -1 This is because the absorption at 100 nm is strong, and does not indicate that Samples 4 to 7 contain a C center.

[0146] (Knoop hardness measurement) Synthetic single crystal diamond / diamond single crystal {001} plane of each sample <100> An indentation was made in the direction of the sample with a load of 4.9 N. The diagonal line a (μm) of the longer side of the indentation was measured, and the Knoop hardness (HK) was calculated using the following formula A. The results are shown in Table 2 under "Synthetic single crystal diamond / single crystal diamond" under "{001} <100> The values ​​are shown in the "Knoop hardness" column. HK=14229×4.9 / a 2 Formula A

[0147] (Breaking strength test) A spherical diamond indenter with R50μm is prepared, and a load is applied to each sample of synthetic single crystal diamond / diamond single crystal at a loading rate of 100N / min at room temperature (23℃), and the load (crack initiation load) at the moment when a crack occurs in the sample is measured. The specific measurement method is described in embodiment 1, so the description will not be repeated. The higher the crack initiation load, the higher the strength of the sample and the better its chipping resistance. The results are shown in the "Crack initiation load" column of "Synthetic single crystal diamond / diamond single crystal" in Table 2.

[0148] [Table 2]

[0149] <Consideration> Sample 2 and Samples 5 to 7 correspond to Examples. Sample 1, Sample 3, and Sample 4 correspond to Comparative Examples. It is confirmed that Sample 2 and Samples 5 to 7 (Examples) have higher hardness and superior chipping resistance than Sample 1, Sample 3, and Sample 4 (Comparative Examples).

[0150] Among the examples, Samples 5 to 7 have particularly high hardness and excellent chipping resistance. This is believed to be because Samples 5 to 7 do not have C centers (isolated substitutional nitrogen atoms) that reduce hardness and strength, and have platelets that contribute to suppressing plastic deformation and crack growth.

[0151] Although the embodiments and examples of the present disclosure have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples may be appropriately combined or modified in various ways. The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]

[0152] 1 Diamond single crystal, 2 Insulator, 3 Carbon source, 4 Solvent metal, 5 Seed crystal, 6 Pressure medium, 7 Graphite heater, 10 Sample chamber

Claims

1. A synthetic single crystal diamond containing nitrogen atoms at a concentration of 100 ppm or more and 1500 ppm or less based on the number of atoms, the synthetic single crystal diamond comprises an aggregate consisting of a vacancy and three substitutional nitrogen atoms adjacent to the vacancy; The Raman shift λ′cm of the peak in the first-order Raman scattering spectrum of the synthetic single crystal diamond -1 and a Raman shift λ cm of a peak in a first-order Raman scattering spectrum of a synthetic type IIa single crystal diamond containing nitrogen atoms at a concentration of 1 ppm or less on an atomic number basis. -1 represents the relationship of the following formula 1: λ'−λ≧0 Formula 1 Synthetic single crystal diamond.

2. 2. The synthetic single crystal diamond according to claim 1, wherein in the fluorescence spectrum of the synthetic single crystal diamond, an emission peak exists in one or both of a fluorescence wavelength range of 415±2 nm and a fluorescence wavelength range of 420 nm or more and 470 nm or less.

3. In the infrared absorption spectrum of the synthetic single crystal diamond, the wave number is 1370 cm -1 Over 1385cm -1 3. A synthetic single crystal diamond according to claim 1 or claim 2, which has an absorption peak within the following range:

4. 4. A synthetic single crystal diamond according to any one of claims 1 to 3, wherein the Knoop hardness in the <100> direction of the {001} face of the synthetic single crystal diamond is 100 GPa or more.

5. 5. A synthetic single crystal diamond according to any one of claims 1 to 4, wherein in a fracture strength test in which a spherical diamond indenter having a tip radius of 50 μm is pressed against the surface of the synthetic single crystal diamond at a load rate of 100 N / min, the crack initiation load is 15 N or more.

6. A method for producing a synthetic single crystal diamond according to any one of claims 1 to 5, comprising the steps of: A first step of synthesizing a diamond single crystal containing nitrogen atoms at a concentration of 100 ppm to 1500 ppm (based on the atomic number) by a temperature difference method using a solvent metal; a second step of irradiating the diamond single crystal with one or both of an electron beam and a particle beam having an energy of 100 MGy to 1000 MGy; A method for producing a synthetic single crystal diamond, comprising: a third step of applying a pressure of 3 GPa or more and a temperature of 1850°C to 2300°C for 1 minute to 3600 minutes to the diamond single crystal after the second step, thereby obtaining the synthetic single crystal diamond.

Citation Information

Patent Citations

  • Manufacture of diamond laser element

    JP1990018980A

  • Synthetic single-crystal diamond

    WO2019077844A1

  • Synthetic single-crystal diamond, tool, and production method for synthetic single-crystal diamond

    WO2019077888A1